2013
DOI: 10.1002/ar.22833
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis and Three‐Dimensional Movement of the Stomach During the Human Embryonic Period

Abstract: The stomach develops as the local widening of the foregut after Carnegie stage (CS) 13 that moves in a dramatic and dynamic manner during the embryonic period. Using the magnetic resonance images of 377 human embryos, we present the morphology, morphometry, and threedimensional movement of the stomach during CS16 and CS23. The stomach morphology revealed stage-specific features. The angular incisura and the cardia were formed at CS18. The change in the angular incisura angle was approximately 90 during CS19 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…Gasser (2006) recently demonstrated most of the positional changes of the developing structures, such as sclerotome formation from the somite, spinal ganglion formation from the neural crest, and endocrine glands formation from the pharyngeal endoderm can be explained by differential growth. We demonstrated 3D positional change of the external ear, stomach, and rotation of intestinal loop via differential growth using 3D coordinates of the anatomical landmarks (Kagurasho et al, 2012, Kaigai et al, 2014, Ueda et al, 2016 (Fig. 4, Video 4: https://players.brightcove.net/656326989001/ default_default/index.html?videoId=5729914912001).…”
Section: Representative Methods For Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Gasser (2006) recently demonstrated most of the positional changes of the developing structures, such as sclerotome formation from the somite, spinal ganglion formation from the neural crest, and endocrine glands formation from the pharyngeal endoderm can be explained by differential growth. We demonstrated 3D positional change of the external ear, stomach, and rotation of intestinal loop via differential growth using 3D coordinates of the anatomical landmarks (Kagurasho et al, 2012, Kaigai et al, 2014, Ueda et al, 2016 (Fig. 4, Video 4: https://players.brightcove.net/656326989001/ default_default/index.html?videoId=5729914912001).…”
Section: Representative Methods For Analysismentioning
confidence: 98%
“…In particular, the branching pattern of the stomach is restricted at both the entrance (C) and the exit (P), which are gradually stabilized after CS20. The stomach deflection is shown by the positional change of M. As a result, the stomach appears to rotate clockwise around the dorso-ventral axis and to move to the left laterally and caudally (Kaigai et al, 2014). (b-i) Illustrations of the anatomical landmarks.…”
Section: Representative Methods For Analysismentioning
confidence: 99%
“…The diffusion tensor map was calculated from seven images (one of them were acquired without MPG) according to the method reported by Basser (Basser and Pierpaoli, 1998), and using the tensor components, mean diffusivity (MD 5 ADC (apparent diffusion coefficient)) and fractional anisotropy (FA) were calculated. Kagurasho et al, 2012;Nakashima et al, 2012;Hamabe et al, 2013;Shiraishi et al, 2013;Kaigai et al, 2014;Shiraishi et al, 2015;Kanahashi et al, 2016;Ueda et al, 2016).…”
Section: Nmr Parameter Calculationmentioning
confidence: 99%
“…Hamabe et al measured 3D morphological property of the liver of eight CS23 embryos and 21 fetuses and clarified the relation between fetal and embryonic livers(Hamabe et al, 2013). property of the stomach of 377 embryos ranging from CS16 to CS23 and clarified 3D movement of the stomach during the periods(Kaigai et al, 2014). Shiraishi et al analyzed the brain of 101 embryos ranging from CS13 to CS23 and precisely visualized the 3D structure of the brain(Shiraishi et al, 2015).Kanahashi et al analyzed the liver of 1,156 embryos ranging from CS14 to CS23 and confirmed nine latent abnormality of the liver that may result in spontaneous abortion(Kanahashi et al, 2016).…”
mentioning
confidence: 99%
“…The video figures are not supplemental material, which eventually may be deleted from server farms. Kaigai et al published the first AR WOW‐Video Article, providing digital movies of the movement of the stomach during the human embryonic period (Kaigai et al, ). The Anatomical Record's second, related publication innovation is interactive 3D PDF figures, which also are permanent by being embedded in the electronic published papers (Ruger Porter and Witmer, ).…”
mentioning
confidence: 99%